Ambipolar and Robust WSe2 Field‐Effect Transistors Utilizing Self‐Assembled Edge Oxides. Issue 1 (3rd December 2019) - Xu, Hao; Han, Xiaoyu; Liu, Wei; Liu, Ping; Fang, Hehai; Li, Xiao; Li, Zhuangnan; Guo, Jian; Xiang, Bin; Hu, Weida; Parkin, Ivan P.; Wu, Jiang; et al.
Abstract: Transition metal oxides (TMOs) with high work function (WF) show promising properties as unipolar p‐type contacts for transition metal dichalcogenides. Here, ambipolar field‐effect transistors (FETs) enabled by bilayer WSe2 with self‐assembled TMOs (WO2.57 ) as contacts are reported. Systematic material characterizations demonstrate the formation of WO2.57 /WSe2 heterojunctions around nanoflake edges with Se atoms substituted by O atoms after air‐exposure, while pristine properties of WSe2 almost sustain in inner domains. As‐fabricated FETs exhibit both polarities, implying WO2.57 with lowered WF at edges can serve as both the p‐type and n‐type contact for inner WSe2 . Noteworthy, greatly reduced contact resistance and enhanced channel current are achieved, compared to the devices without WO2.57 contacts. Linear drain–source current relationship from 77 to 300 K indicates the ohmic contact between edge WO2.57 and inner WSe2 . Density functional theory calculations further reveal that the WO2.57 /WSe2 heterojunction forms a barrier‐less charge distribution. These nm‐scale FETs possess remarkable electrical conductivity up to ≈2600 S m −1, ultra‐low leakage current down to ≈10 −12 A, robustness for high voltage operation, and air stability, which even outperform pristine WSe2 FETs. Theoretical calculations reveal that the high conductivity is exclusively attributed to the air‐induced WO2.57 and its further carrier injection to WSe2 . Abstract : Field‐effect transistors (FETs) based on air‐induced self‐passivated bilayer WSe2 are reported. Systematic material characterizations validate the formation of WO2.57 /WSe2 heterojunctions around edges of WSe2 while pristine WSe2 remains in inner domains. With WO2.57 working as the contact for WSe2, FETs possess ohmic contact and ambipolar behavior, high conductivity, ultra‐low leakage current, and less sensitivity to ambient conditions.